Mãos negras em solo hostil : a luta do trabalhador negro representada pelos escritos de Feliciano Galdino de Barros nos jornais de Cuiabá na Primeira República - Silva, Cristiane dos Santos (2020)
The present thesis has as research object the analysis of the participation of Feliciano Galdino de Barros in the struggle of the black worker and the small black producer for citizenship through newspaper articles in Mato Grosso State, in order to reconstruct the daily life of the free rural black in the First Republic and the political clash reproduced through the press, according to the perspective of its writers. The thesis aims to reconstitute the rural universe in which workers were active historical subjects, and were at the mercy of the most diverse violence, such as the lack of access to education, work, land and its regularization and, to political participation, immersed in a literate world that it propagated an exclusive discourse that reinforced the attempt of marginalization and inferiorization of the black worker. Black workers formed alliances and affiliated with workers' associations and political parties, in order to strengthen their struggle for rights and social recognition. Black workers did not write newspaper articles, but allied themselves with a group of intellectuals, who, in their writings, questioned and denounced the repressive forms employed by rural oligarchies headed by rich landowners in the region. Among the intellectuals, I highlight the political trajectory of Feliciano Galdino de Barros, primary teacher and union leader, who wrote in 1922, in the newspaper A Cruz, about the attacks against the black community of Mata Cavalo, in Livramento. The reports recorded in the newspapers, added to the existing clues in the documentary sources, detail the arbitrary actions of the rural oligarchy allowing an in-depth study of the process of raising awareness and resistance of workers and rural producers for their rights, for their identity and their place of belonging.